Voices From the Periphery: Lived Experiences of Women International Students From the Global South Studying at U.K. Universities - Schartner, Alina; Shields, Samantha; Wang, Yao (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
Critical and intersectional perspectives on international student mobility (ISM) are burgeoning; however, gendered aspects are still rarely examined. This paper offers a contribution to this lacuna and provides further understanding of how gender shaped the experiences of six women international students from the Global South. The women participated in episodic narrative interviews as part of a wider study analyzing ISM in relation to socioeconomic status (SES). Women constitute more than half of the international students in the U.K., reflecting aspects of the feminization of migration. Consequently, the narratives were critically interrogated as to the extent to which the women were aligned with the “postfeminist subject.” However, the extent to which the women were “freely choosing” and “self-reinventing” is contested, in relation to choices, financial independence, and career aspirations. The findings indicated that there was a realignment of “success” upon near completion of educational qualifications which reflect gendered inequalities in society. Therefore, “neoliberal feminism” may be a more effective way in which to theorize an “ideal” of a balance between the imagined future identity of a “strong, independent career woman” with naturalized aspects of femininity for women international students.